Kecurangan Laporan Keuangan - Ahmad Basid; Karina Odia Julialevi; Rishi Septa Saputra; Nanik Rahayu; Moh. Wahyudin Zarkasyi; Srihadi Winarningsih; Citra Sukmadilaga (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Financial statements provide a comprehensive overview of an entity's performance over a specific period. The accurate and proper presentation of these statements, in accordance with established accounting standards, is crucial for enabling decision-makers to make informed and effective decisions. However, instances of fraud in financial reporting by top management and accountants continue to be observed. This webinar aims to shed light on common patterns of fraudulent financial statements within organizations, addressing perspectives from both academic and practitioner viewpoints. Strong corporate governance plays a vital role in establishing adequate control systems that help minimize the risk of fraudulent financial reporting. Additionally, segregating duties and authorities is essential in reducing the risk of financial misstatements. Fraud detection can be effectively conducted through financial ratio analysis, both vertical and horizontal, as well as forensic and digital data analysis techniques